Molecular characterisation of drug-resistant Plasmodium falciparum from Thailand - Lopes, Dinora (BioMed Central, 2002)
BACKGROUND: The increasing levels of Plasmodium falciparum resistance to chloroquine (CQ) in Thailand have led to the use of alternative antimalarials, which are at present also becoming ineffective. In this context, any strategies that help improve the surveillance of drug resistance, become crucial in overcoming the problem. METHODS: In the present study, we have established the in vitro sensitivity to CQ, mefloquine (MF), quinine (QUIN) and amodiaquine (AMQ) of 52 P. falciparum isolates collected in Thailand, and assessed the prevalence of four putative genetic polymorphisms of drug resistance, pfcrt K76T, pfmdr1 N86Y, pfmdr1 D1042N and pfmdr1 Y1246D, by PCR-RFLP. RESULTS: The percentage of isolates resistant to CQ, MF, and AMQ was 96% (50/52), 62% (32/52), and 58% (18/31), respectively, while all parasites were found to be sensitive to QUIN. In addition, 41 (79%) of the isolates assayed were resistant simultaneously to more than one drug; 25 to CQ and MF, 9 to CQ and AMQ, and 7 to all three drugs, CQ, MF and AMQ. There were two significant associations between drug sensitivity and presence of particular molecular markers, i) CQ resistance / pfcrt 76T (P = 0.001), and ii) MF resistance / pfmdr1 86N (P < 0.001) CONCLUSIONS: i) In Thailand, the high levels of CQ pressure have led to strong selection of the pfcrt 76T polymorphism and ii) pfmdr1 86N appears to be a good predictor of in vitro MF resistance.